What's Next for Information World Mapping?: International and Multidisciplinary Uses of the Method. Issue 1 (13th October 2021) - Greyson, Devon; Tsai, Tien‐I; Kitzie, Vanessa; Martzoukou, Konstantina; Mabi, Millicent
Abstract: As use of arts‐involved and data visualization methods increases in information science, it is important to reflect on strengths and weaknesses of various methods. In this 90‐minute panel, an international lineup of information researchers will share their experiences using the participatory, visual elicitation technique information world mapping (IWM) in their work. Panelists will discuss ways to adapt the technique to different contexts, share their thoughts on what is next for IWM, and raise questions regarding challenges and new uses of IWM in information research. Presentations will be followed by an interactive discussion among panelists and Q&A period with the audience.